Adaptation Strategies of Papuan Students in Secondary Education Affirmation: Strategi Adaptasi Siswa Papua dalam Program Afirmasi Pendidikan Menengah - Hati, Kusuma; Trinugraha, Yosafat Hermawan (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines cross-cultural student adaptation within an educational affirmation context. General Background: Educational equity remains a major challenge in Indonesia, particularly in Papua, prompting the establishment of the Secondary Education Affirmation Program (ADEM) to expand access to quality secondary education outside the region. Specific Background: Papuan students at SMA Negeri 1 Ngemplak Boyolali face linguistic, academic, social, and cultural challenges during their transition. Knowledge Gap: Although ADEM implementation has been discussed in prior research, limited studies analyze students’ adaptation strategies using John William Bennett’s adaptation framework within a specific school setting. Aims: This study analyzes behavioral, strategic, and process-based adaptation strategies of Papuan students and examines the role of schools and teachers in supporting integration. Results: Using a qualitative case study with interviews, observation, and documentation, findings show that students apply behavioral adjustments, tactical learning strategies, and gradual adaptive processes consistent with Bennett’s model, supported by peer networks, inclusive instruction, differentiated learning, and structured mentoring. Novelty: This study contextualizes Bennett’s adaptation theory within an affirmation-based secondary education setting. Implications: The findings provide practical guidance for strengthening institutional support, culturally responsive pedagogy, and mentoring systems to sustain equitable integration of culturally diverse learners. Highlights• Learners navigate cross-regional transition through observable social and classroom adjustments.• Independent learning planning and collaborative networks support academic participation.• Institutional inclusivity and mentoring structures foster sustainable integration. Keywords: Strategies; Secondary Education Affirmation Program; Papuan Students; Cross Cultural Education; Inclusive School Environment